An unpredictable complication during percutaneous endoscopic tube placement: Esophageal perforation - Ağan, Ahmet Faruk (Georg Thieme Verlag KG, 2014)
A percutaneous endoscopic gastrostomy (PEG) was performed to provide an enteral feeding route. Major and minor complications related to this procedure include, aspiration, wound infections, necrotizing fasciitis, peritonitis, abscess, peristomal leakage, pneumoperitoneum, ileus, portomesenteric venous gas, colon injury, gastrocolocutaneous fistulae, abdominal wall bleeding, intra-abdominal bleeding, gastric outlet obstruction, inadvertent gastrostomy tube removal, spleen trauma, clogged PEG tube, tumor implantation at PEG site, and buried bumper syndrome [1, 2].
WOS: 000343106300032
PubMed ID: 25314168
Keywords: Percutaneous Endoscopic Tube Placement; Esophageal Perforation; Complication